جربة على هامش مهرجانها للفيلم الاسطوري والتاريخي - قوجة, محمد (Al-Jazira | الجزيرة, 1999)
Number: 139
Keywords: Vie culturelle – Djerba

جربة على هامش مهرجانها للفيلم الاسطوري والتاريخي - فوجة, محمد (Al-Jazira, 1999)

‎⁨14 دولة تشارك في مهرجان جربة الدولي الفيلم الاسطوري والتاريخي⁩ (الإتحاد, 1999)
Keywords: Vie culturelle – Djerba

Savoir-faire français : la réussite de Djerba - Pinçon, Jean-Marie; Barbaccia, Annie (Le Figaro, 1999)
Keywords: Tourisme – Djerba

La douce tunisienne : Djerba - Charbonneau, Jean-Paul (La Presse, 1999)
Keywords: Récits de voyage – Djerba

La bataille de Djerba - Scemama, Corinne (L'Express, 1999)

Djerba an oasis for tourists since Ulysses time - Schultz, Judy (Kingston Whig, 1999)
Keywords: Tourisme – Djerba

Djerba: Island of the Lotus Eaters - Schultz, Judy (Edmonton Journal, 1999)
4 parties
Keywords: Tourisme – Djerba

Moufida Tlatli et les Pénélope de Djerba - Baudin, Brigitte (Le Figaro, 1999)

Tunisian Picnic: Chef Abderrazak Haouari Holds Court in Djerba - Mallet, Gina (National Post, 1999)
Keywords: Vie culturelle – Djerba